Literature Review : Penambahan Jantung Pisang dan Rebung pada Abon Ikan untuk Hipertensi - Silva Zurinah; Arya Ulilalbab (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Hypertension is a significant global health problem, especially in specific groups such as pregnant women. The high incidence and potential for serious complications demand non pharmacological management efforts and innovative use of local foods. This study examines the potential of local functional foods such as Ambon bananas, banana blossoms, and bamboo shoots as alternatives for health management and product development, particularly those related to hypertension in pregnant women. The method used was a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, which encompasses four main stages: identification, screening, feasibility assessment, and analysis of results.The study results showed that the Ambon banana diet significantly reduced systolic and diastolic blood pressure. Factors such as age, family support, stress levels, and fast food consumption were shown to be significantly associated with the incidence of hypertension in pregnant women. Furthermore, bamboo shoot consumption significantly reduced blood cholesterol levels and blood pressure. In terms of product innovation, the fish floss formulation combined with banana blossoms or bamboo shoots received positive feedback from the panelists. The fermentation process of bamboo shoots is known to produce flour with a very high crude fiber content. Therefore, this local food has significant potential as a source of additional fiber and a raw material for value-added processed products to support food security and improve public health.